Understanding Accent and Identity on the Border: Exploring Bilinguals’ Perceptions of Intelligibility, Accentedness, and Language-Learning Goals - Shannon McCrocklin (Ilha do Desterro)
Although the field of second language (L2) pronunciation teaching has moved toward intelligibility models and goals, several studies have shown that many L2 learners still profess a desire to sound native-like in their L2. This study explores the perspectives of bilinguals who have navigated their accent and identity in two different languages to explore the impact of increasing recognition of links between accent and identity on language-learning goals. Findings show that almost all bilingual participants (97%) recognized links between accent and identity, yet 72% still reported preferring a native accent if they learned a new language today. Intelligibility emerged as a key issue, with those wanting a native accent linking nativeness to increased intelligibility while those rejecting native accents separating the two dimensions (accent and intelligibility) while prioritizing intelligibility.